An 8-Years-Old Child With Post Streptococcal Related Acute Glomerulonephritis Accompanied By Pleural Effusion: Case Report - Yuan Agita Aprilia R; D, Adivia Cheries (Syntax Corporation Indonesia, 2024)
The inflammatory process in the glomerulus caused after infection from group A nephritogenic type beta-hemolytic streptococcal bacteria is called acute post-infectious streptococcal glomerulonephritis (GNAPS). Patients who exhibit symptoms such as gross hematuria, puffiness, and hypertension, as well as acute renal failure after streptococcal infection, should suspect post-streptococcal acute glomerulonephritis. Typical signs of glomerulonephritis in urinalysis, evidence of laboratory streptococcal infection (ASTO more than 100 Todd), and low levels of C3 complement (less than 4 years or more than 15 years) have a history of disease with similar symptoms, accompanied by chronic renal failure, GFR below 50% of normal age, macroscopic hematuria more than 3 months or microscopic hematuria more than 1 year, C3 levels decrease over 3 months as well as refractory proteinuria. Administration of antibiotics (Penicillin for 10 days) in the acute phase does not affect the worsening of the condition of glomerulonephritis but rather reduces the spread of Streptococcal infections that may still exist. In addition, treatment of hypertension is also necessary. Peritoneal measures of dialysis or hemodialysis may be considered in cases of acute renal failure.